The Coherence Effect: Blending Cold and Hot Cognitions. - Simon, Dan; Stenstrom, Douglas M.; Read, Stephen J. (Journal of Personality & Social Psychology, 2015)
Previous research has shown that making complex judgments and decisions entails a mental reconstruction of the task in a way that increases the state of coherence between the emerging conclusion and its underlying attributes: The attributes that support the conclusion grow stronger, whereas the attributes that support the losing option weaken. This coherence effect is understood to occur bidirectionally, in that conclusions follow from the decision-maker's evaluation of the attributes, while the evaluations of the attributes shift to cohere with the emerging conclusion. The current studies were designed to extend the coherence effect to encompass cognitions that could be considered "hot," such as valence evaluations, motivation toward outcomes of events, liking and disliking of actors, and emotions toward actors. Study 1 found that evaluations of a complex social relationship were accompanied not only by supportive interpretations of the ambiguous facts, but also by concordant hot cognitions. Studies 2 through 4 included manipulations to demonstrate the spreading of coherence from cold to hot cognitions and in the opposite direction. We observed these effects following a manipulation of the facts (Study 2), a manipulation of participants' emotions toward the actor (Study 3), and a manipulation of participants' motivation toward the outcome of the case (Study 4). These results support the proposition that complex judgments and decisions are performed by coherence-based reasoning: a holistic, connectionist process that maximizes coherence among and between the myriad of factors involved in the tasks and the hot cognitive reactions to them.